A tie that blinds: family and ideology in Ireland - McCullagh, Ciaran (Economic & Social Studies, 1991)
This paper examines the origins of the role of the family as a social symbol in Irish society. The source, it argues, is in the nature of the inequalities that were present in late nineteenth- and early twentieth-century Ireland. These were not simply through classes but also through families. The ideology of the family emerged to deny and to displace the tensions created by the nature of these kinds of inequalities.
Keywords: family; society; social history; Ireland